Morphological and morphometric study of greater palatine foramen in dry skulls of Eastern Indian population - Mukhopadhyay Paramita; Sarbani Das; Biswas Sharmistha; Mukherjee Parijat; Bhakta Abhijit (Wolters Kluwer Medknow Publications, 2024)
Background: Greater palatine foramen (GPF) transmits important neurovascular structures which may get injured during different operative procedures such as intraoral maxillary nerve block, cleft palate repair, and operative procedures involving maxillary sinus and maxillary molars. Hence, proper knowledge about the GPF is very essential. The aim of this study was to study the shape of GPF and its location in relation to molar tooth, measure the diameters of GPF, and measure the distances of GPF from different landmarks of palate. Methodology: A dry bone-based study was conducted on dry human skulls of Eastern Indian population using digital Vernier caliper. At first location of GPF in relation to maxillary molars was noted, followed by anteroposterior (AP) and transverse diameter of GPF and distance of GPF from incisive fossa, posterior border of hard palate (PBHP) and interpalatine suture was measured. Results: In 69.64% of cases, GPF was present medial to the maxillary molar tooth and most common shape is oval type which is found in 44.64% of cases. AP diameter was almost same in both the sides which is 5.13 mm in average and transverse diameter is 2.91 mm. The mean distance of GPF from incisive fossa, PBHP, and interpalatine suture (IPS) is as follows in sequence, 37.24 mm, 3.21 mm, and 13.68 mm. Conclusion: The findings from the present study can be used as a guide for locating GPF during different operative procedures such as palatal reconstruction in cleft palate, maxillary surgeries, and intraoral maxillary nerve block. GPF is located about 3 mm in front of PBHP, most commonly medial to the third maxillary molar, about 15 mm lateral to IPS in the present study among Eastern Indian population.